Cooperative strategies of accommodation facilities: a driving force to enhance secondary tourism resources ? - Remondino, Marco (Piccola Impresa / Small Business, 2021)
The topic of this paper is enhancing destination competitiveness, with particular interest to entrepreneurial strategies able to valorise secondary attractions. A literature review reveals that, by means of cooperation, local stakeholders could increase success of mass destinations, while promoting the discovery of niche attractions, with a positive impact on the whole territory. Also, the role of DMOs is important, facilitating the cooperation between the public and private sectors and among private companies. Destination branding strategies could be set, to define the competitive advantages of a territory, leveraging on synergies among primary and secondary attractions. The specific case study of Liguria is proposed and analysed by means of a questionnaire, spread among potential tourists. This Italian region has a tourism concentrated during summertime (bathing season), but possesses other specific features, that could differentiate the offer and potentially attract tourists also in other periods. The questionnaire, in fact, reveals that many tourists also like to explore the inland, which should therefore be further promoted. It also emerges than about 9% of tourists didn’t take advantage of secondary tourism products, not being aware of them, while about 46% believe that secondary attractions could be interesting for tourism, but are not adequately exploited, due to the lack of both strategic cooperation among local businesses and direct promotion.